2016
DOI: 10.1021/acs.analchem.6b00265
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Mapping of Sialic Acid Linkage Isomers by Ion Mobility Spectrometry

Abstract: Detailed structural elucidation of protein glycosylation is a tedious process often involving several techniques. Glycomics and glycoproteomics approaches with mass spectrometry offer a rapid platform for glycan profiling but are limited by the inability to resolve isobaric species such as linkage and positional isomers. Recently, ion mobility spectrometry (IMS) has been shown to effectively resolve isobaric oligosaccharides, but the utility of IMS to obtain glycan structural information on a site-specific lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 48 publications
3
76
1
Order By: Relevance
“…The CCS values reflect the rotationally averaged structures that are the basis of the assignment of glycopeptide species. The isomers are distinguished based on their drift times, and the linkages of sialic acid residues are determined according to the peak differences derived from before and after specific exoglycosidase treatment . Also, isomeric glycopeptides with two distinct glycosylation sites can be separated by IM‐MS .…”
Section: Glycopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCS values reflect the rotationally averaged structures that are the basis of the assignment of glycopeptide species. The isomers are distinguished based on their drift times, and the linkages of sialic acid residues are determined according to the peak differences derived from before and after specific exoglycosidase treatment . Also, isomeric glycopeptides with two distinct glycosylation sites can be separated by IM‐MS .…”
Section: Glycopeptidesmentioning
confidence: 99%
“…It is difficult to determine the glycopeptides containing sialylation variants or sharing the same glycan compositions in distinct glycosylation sites. A promising technique capable of improving the identification is IM-MS. 147,148 In IM-MS, analyte ions traverse a region of neutral gas under the influence of a weak electric field and undergo a series of low-energy collisions with the gas. As a result, the ions are separated according to their mass, charge, size, and shape.…”
Section: Im-ms For Glycopeptidesmentioning
confidence: 99%
“…161 In this study, it was also demonstrated that fragment ions produced via CID from a tryptic digest of a glycopeptide indicated that α 2,3 and α 2,6 sialylation ratios in their arrival time distributions (ATD) can provide additional information on the presence, or absence, of antennary sialo-glycoforms. 161 With recent advancements in automated carbohydrate synthesis, authentic standards should soon become more readily available and thereby allow in the coming years for the definitive identification of unknown multiantennary sialic acid isomers based on the matching of cross section and m / z values provided from such experiments.…”
Section: Role Of Ion Mobility Spectrometrymentioning
confidence: 78%
“…IM-IM-MS was recently used to distinguish underivatized carbohydrate isomers based on differences in mobilities of fragments ions. By probing ion mobility profiles of product ions, IM was also used to distinguish α2,3 or α2,6 sialic-acid linkage [15,43]. …”
Section: Coupling Im With Ms-based Fragmentation and Spectroscopic Tementioning
confidence: 99%
“…For example, IM can separate intact glycopeptides that differ only in the glycosylation sites [16]. Furthermore, IM-MS analysis of glycopeptide fragments was demonstrated to be an effective strategy to distinguish α2,3 versus α2,6 sialic acid linkages on intact glycopeptides [15,16]. In addition to glycopeptides, IM-MS was recently used to separate glycolipid isomers [57].…”
Section: Improved Characterization Of Intact Glycoconjugatesmentioning
confidence: 99%